Acute pancreatitis in patients with COVID-19 is more severe and lethal: a systematic review and meta-analysis. (2nd December 2021) - Mutneja, Hemant Raj; Bhurwal, Abhishek; Arora, Shilpa; Goel, Akshay; Vohra, Ishaan; Attar, Bashar M.
Abstract: Background: Emerging evidence suggests an association between acute pancreatitis and COVID-19. Our objective is to conduct a systematic review and meta-analysis to evaluate whether COVID-19 affects the severity and outcomes associated with acute pancreatitis. Methods: Cochrane guidelines and PRISMA statement were followed for this review. Digital dissertation bases were searched and all studies comparing the outcomes of acute pancreatitis amongst patients with and without COVID-19 were included. We compared the etiology, severity, length of hospital stay and mortality associated with acute pancreatitis in patients with and without COVID-19. Results: Four observational studies with a total of 2, 419 patients were included in the review. Presence of COVID-19 significantly increased the odds of mortality (OR 4.10, 95% CI 2.03–8.29) in patients with acute pancreatitis. These patients also had an increased incidence of severe pancreatitis (OR 3.51, 95% CI 1.19–10.32), necrotizing pancreatitis (OR 1.84, 95% CI 1.19–2.85) and a longer length of hospital stay (OR 2.88, 95% CI 1.50–5.52), compared to non-COVID patients. Patients with COVID-19 were more likely to have an unknown or idiopathic etiology of acute pancreatitis (OR 4.02, 95% CI 1.32–12.29), compared to non-COVID-19 patients. Conclusion: Current evidence suggests that COVID-19 adversely impacts the morbidity and mortality associated with acute pancreatitis. SARS-CoV-2 may be a causative agent for acute pancreatitis. Further population-based studies are needed to confirm or refute these findings.